Candida Albicans Osteomyelitis after Chest Wall Blunt Trauma: A Case Report. (3rd June 2021) - Minervini, Fabrizio; Kestenholz, Peter B.; Fritsche, Elmar; Franchi, Alberto
Abstract : Fungal osteomyelitis is a rare disease that can occur in immunocompromised patients. We report a case of a patient with a primary rib osteomyelitis after a blunt trauma of the chest wall. Aggressive surgical debridement along with antifungal therapy was the cornerstone of the disease management in this patient.